Media Modifikasi Piring Plastik Untuk Meningkatkan Efektivitas Belajar Lempar Cakram - Hari Bowo, Yudho Ranto (Jurnal Dewantara, 2016)
Infrastructure is a strategic part in the achievement of learning objectives. In other words, complete and incomplete infrastructure also affects the maximum learning and not maximum achievement of learning objectives. Means complete can facilitate teachers to pursue specific targets into learning goals. Based on observations of student activity on two cycles of research on learning Discus Throw with plastic plates showed an increase in activity of students from the first cycle to the second cycle. It is seen that the first cycle of student activity reaches 70%, then in the second cycle to reach 85% this means that there is a 15% increase after treathment or improvement in the second cycle, so that the average activity of students during two cycles is 75%.